2016
DOI: 10.3354/dao02971
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological alterations of the heart in fish: proposal for a standardized assessment

Abstract: Histopathological alterations in the heart are often reported in fish as a result of exposure to a variety of chemical compounds. However, researchers presently lack a standardized method for the evaluation of histopathological alterations in the cardiovascular system of fish and the calculation of an 'organ index'. Therefore, we designed a method for a standardized assessment and evaluation of histopathological alterations in the heart of fish. As a model species, we used rainbow trout Oncorhynchus mykiss, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Partial fish meal replacement with processed insect meal without negative effect on the growth of salmonids was reported Gasco et al (2014), who successfully replaced up to 50% of fish meal with mealworm larva meal, and Stamer et al (2014), who used BSF meal in the rainbow trout diet. Fish meal replacement with insect meal ≥50% was associated with significantly reduced growth in the majority of studies (St-Hilaire et al 2007b, Sealey et al 2011, Stamer et al 2014, although total FM replacement with BSF meal without deterioration of growth parameters was reported by Lock et al (2014) in Atlantic salmon. Potential utilization of live or raw insects in salmonid mass culture is problematic; however, a collaboration of fish and insect farming may be possible with local producers.…”
Section: Tablementioning
confidence: 96%
See 1 more Smart Citation
“…Partial fish meal replacement with processed insect meal without negative effect on the growth of salmonids was reported Gasco et al (2014), who successfully replaced up to 50% of fish meal with mealworm larva meal, and Stamer et al (2014), who used BSF meal in the rainbow trout diet. Fish meal replacement with insect meal ≥50% was associated with significantly reduced growth in the majority of studies (St-Hilaire et al 2007b, Sealey et al 2011, Stamer et al 2014, although total FM replacement with BSF meal without deterioration of growth parameters was reported by Lock et al (2014) in Atlantic salmon. Potential utilization of live or raw insects in salmonid mass culture is problematic; however, a collaboration of fish and insect farming may be possible with local producers.…”
Section: Tablementioning
confidence: 96%
“…Inclusion of the black soldier fly, Hermetia illucens (BSF), larvae and mealworm, Tenebrio molitor, has been assessed in salmonid diets. Replacement of 25% to 50% of the FM with BSF meal in a rainbow trout diet showed no significant effects on weight gain and feed conversion ratio but resulted in lower levels of omega-3 fatty acids in fillets (St-Hilaire et al 2007b, Stamer et al 2014. Sealey et al (2011) reported satisfactory growth of rainbow trout fed a diet replacing 50% of FM with BSF reared on manure enriched with trout offal, while a diet containing BSF reared on manure only was associated with significantly slower growth compared to the commercial diet.…”
Section: Introductionmentioning
confidence: 99%
“…This communication also highlights some of the limitations of the histological scoring systems applied to date: A comprehensive, organ‐by‐organ protocol is currently lacking. Studies have classically included gills, liver, kidney and skin, only (Bernet et al 1999; Steinbach et al 2016). Most of the scoring systems have been focused on the effects of pollution and contamination (Bernet et al 1999; Au 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Bernet et al (1999) developed a histopathological scoring system in fish that has been widely used across the literature (Zimmerli et al 2007; Poleksic et al 2010; Saraiva et al 2015; Steinbach et al 2016; Gregorc et al 2018; Lei et al 2018), with more than 800 citations in Google Scholar ® and 450 citations in Web of Science ® (Table 1). Originally, this system was designed to assess changes induced by aquatic pollutants on the most susceptible organs (gills, kidney, liver and skin) and did not include other tissues susceptible to alteration by other different disease processes.…”
Section: Potential Aspects To Standardize and Common Limitations In Fmentioning
confidence: 99%
See 1 more Smart Citation